Struktur komunitas makroarthropoda tanah di lahan pertanian durian di kawasan Gunungpati - Febri Edo; Udi Tarwotjo; Rully Rahadian (Jurnal Biologi Tropika, 2019)
The objective of this study is to compare community structures, which include diversity, abundance, evenness, and macroarthropod dominance of monoculture durian farmland, polyculture durian farmland and non-durian farmland (arabica coffee) in Gunungpati region. This research is an exploratory observation carried out from February to March 2019. Samplingwas done using pitfal trap. The identification of samples was carried out in the Diponegoro University Ecology and Biosystematics laboratory. Data analysis was carried out by calculating diversity index (H'), evenness (e), dominance (D), richness, Sorenson test and Hutcheson t-test. The results showed that arthropods in monoculture farmland were found 195 individuals, in polyculture farmland were found 181 individuals and in arabica coffee farmland were found 229 arthropods. Diversity index (H') and evenness (e) in monoculture farmland were lower than in polyculture farmland and arabica coffee farmland. The three areas are dominated by the family Formicidae. The three fields have a high degree of similarity. Overall 8 families were found as predators, 4 families as herbivores, 3 families as detritivores and 1 family as decomposers.